P234 Relationship between demand and control to the nutritional status workers of the court of justice of minas gerais state, brazil. (1st September 2016) - Costa, Bruna; Lima, Eduardo; Assunção, Ada
Abstract : Social pressure, work overload, high level of productivity requirement and lack of recognition and autonomy are factors that affect the nutritional status of workers. This study aims to estimate the nutritional profile and assess its association with psychosocial factors in a sample of workers of the Court of Justice of Minas Gerais State, Brazil. A cross-sectional study with a probabilistic sample of workers (pregnant individuals and those on vacation or away for other reasons for excluded), is being conducted through telephone interview (data collection finishes at march 2016), in order to provide socioeconomic, health and psychosocial data. Self-reported information on weight and height will be used to estimate worker's body mass index and allow nutritional status classification. The translated, adopted and validated in Portuguese version of the Swedish Demand-Control-Support Questionnaire will be used to address the psychosocial factors. Estimates of nutritional status will be presented by sex, age and education. Linear regression models will be used to evaluate the association between nutritional status and psychosocial factors. This survey results will provide an unprecedented assessment of nutritional status of the judiciary workers of Brazil as well as it work related associated factors.